MENAKAR KEBERLANJUTAN PROGRAM KUBE: PELUANG DAN TANTANGANPROGRAM KUBE DALAM PEMBERDAYAAN MASYARAKAT MISKIN PERKOTAANDI KELURAHAN KEPARAKAN, KECAMATAN MERGANGSAN, KOTAYOGYAKARTA - Aprilianti, Laras; Astuti, Eka Zuni Lusi (UI Scholars Hub, 2019)
KUBE is one of the poverty alleviation programs under the Directorate of Social Empowerment and Poverty Reduction, Ministry of Social Affairs. This program aims to empower the poor groups through the financial assistance to support productivity in economy. KUBE in Keparakan Village, Mergangsan, Yogyakarta City is one of the KUBE in DIY Province which is the best KUBE candidate in DIY. Ironically, within 3 years implementation of the KUBE Program, from 6 KUBE, 4 KUBE sustainable and the other 2 was discontinued. This paper seeks to examine what are the supporting and inhibiting factors for the implementation of sustainability KUBE in Keparakan Village.SWOT analysis and indicator of KUBE’s sustainability from the government can be used to interpret the causes of sustainable and discontinued KUBE.This research is using descriptive qualitative method and the data is collected using observation, deep interview, documentation, and audio visual. The results show that the internal factors gave the biggest impact for the sustainability of KUBE in Keparakan Village.All these sustainable KUBE has strong internal factors. It is reflected by the member’s commitment to obey the rules of the group. On the other hand, the discontinued KUBE has weak internal factors for its member ignorance to the rules. Besides, the role from KUBE facilitator wasn’t optimal enough to solve the problems faced by two discontinued KUBE.